An updated checklist of the herpetofauna of Querétaro, Mexico: species richness, diversity, and conservation status - Cruz-Elizalde, Raciel; Ramírez-Bautista, Aurelio; Hernández-Salinas, Uriel; Berriozabal-Islas, Christian; Wilson, Larry David (Zootaxa, 2019)
Mexico contains a large number of amphibian and reptile species, and the states in the southeastern part of the country are the richest and most diverse. Although the study of species richness within Mexico’s individual states has been increasing over the last two decades, herpetofaunal species lists for several states in the central region are incomplete. Herein, we provide a list of the herpetofauna of the state of Querétaro, a state that remains relatively unexplored. We also indicate the conservation status of the component species in the state, based on the national and international categorizations, as well as their Environmental Vulnerability Scores (EVS). Based on a review of literature and specimens in scientific collections, our results show that the herpetofauna of Querétaro currently is composed of 138 species, of which 34 are amphibians (27 anurans and seven caudates) and 104 are reptiles (three turtles, 34 lizards, and 67 snakes). The number of Mexican endemic species occurring in the state consists of 19 amphibians and 50 reptiles, representing 55.9% and 48.1%, respectively, of the total numbers in these groups. A total of 61 species (13 species of amphibians and 48 of reptiles) are listed in NOM-059-SEMARNAT-2010, within the categories of Special Protection (Pr) and Threatened (A). According to the International Union for Conservation of Nature (IUCN 2019), 34 species of amphibians (100% of species) and 87 species of reptiles (83.65% of a total of 104) have been placed within a risk category, i.e., except for the DD and NE categories. The EVS results show that nine species of amphibians have high environmental vulnerability, 11 species medium vulnerability, and 14 low vulnerability, whereas among the reptiles, 22 species have high vulnerability, 43 medium vulnerability, and 37 species low vulnerability. The herpetofauna of Querétaro illustrates a high level of species richness, which is typical of central Mexico, as well as diverse groupings associated with the arid, temperate, and tropical environments found in the state. These types of studies are necessary for increasing our knowledge of the herpetofauna in the various states of Mexico, as well as for evaluating the conservation status and implementing management plans for species in both herpetofaunal groups.